Scratch Adhesion and Wear Failure Characteristics of PVD multilayer CrTi/CrTiN Thin Film Ceramic Coating Deposited on AA7075-T6 Aerospace Alloy - Quazi, M. M.; M., Ishak; Arslan, A.; M. Nasir, Bashir; Imran, Ali (Taylor & Francis, 2018)
This study highlights the scratch adhesion failure characterization and tribo-mechanical properties of physical vapor deposited (Cr, Ti) N coating on AA7075-T6 by using magnetron-sputtering technique. The surface morphology, microstructure and chemical composition of CrTi/CrTiN fim were inspected by an optical microscope, scanning electron microscope (SEM) incorporated with energy dispersive X-ray spectroscopy (EDX) in addition to focused ion beam milling. The coating to substrate critical load of about 1261 mN was obtained, by employing coating deposition parameters of; DC power (300 W, RF power (200 W)), temperature (300 °C) and nitrogen flw rate (6%). Failure adhesion characteristics exhibited initial arc-tensile cracking followed by chipping and spallation that led to complete coating failure at Lc3. The tribo-mechanical aspects were evaluated by a pinon-plate reciprocating testing unit, which showed a lower friction coeffient of 0.36 for CrTiN as compared with 0.43 for AA7075-T6. Subsequently, the wear depth was also reduced from 9.5 to 5.9 μm. It was revealed that the wear mechanism for AA7075-T6 was extensive deformation, abrasion and delamination, while the CrTiN exhibited slightly oxidative abrasive wear mode.